2023
DOI: 10.1021/acsami.2c19944
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ferroelectricity of Paraelectric Oxides Tailored by Nano-Engineering

Abstract: Inducing clear ferroelectricity in the quantum paraelectric SrTiO 3 is important for triggering methods to discover hidden phases in condensed matter physics. Several methods such as isotope substitution and freestanding membranes could introduce ferroelectricity in SrTiO 3 toward nonvolatile memory applications. However, the stable transformation from quantum paraelectric SrTiO 3 to ferroelectricity SrTiO 3 at room temperature still remains challenging. Here, we used multiple nano-engineering in (SrTiO 3 ) 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It can be concluded by the theoretical study that when the O 2p bands were far away from the Fermi level in comparison to the Ru 4d bands, the lattice oxygen was greatly limited and the OER mechanism tended to the adsorbate evolution mechanism (AEM). 78 In contrast, when the O 2p band center got close to the Ru 4d orbital center, the lattice oxygen at the catalyst surface was more likely to take part in the reaction and the OER mechanism was inclined to the lattice oxygen evolution mechanism (LOM) (Fig. 3d).…”
Section: The Relationship Between Reaction Mechanisms and Activitymentioning
confidence: 99%
“…It can be concluded by the theoretical study that when the O 2p bands were far away from the Fermi level in comparison to the Ru 4d bands, the lattice oxygen was greatly limited and the OER mechanism tended to the adsorbate evolution mechanism (AEM). 78 In contrast, when the O 2p band center got close to the Ru 4d orbital center, the lattice oxygen at the catalyst surface was more likely to take part in the reaction and the OER mechanism was inclined to the lattice oxygen evolution mechanism (LOM) (Fig. 3d).…”
Section: The Relationship Between Reaction Mechanisms and Activitymentioning
confidence: 99%
“…OER occurs at the anode and is the rate-limiting step in the H 2 production process by water electrolysis. Specically, OER is a four-electron transfer process with a very complex mechanism (e.g., AEM or LOM), 33,34 and a slow kinetic reaction, resulting in a high overpotential.…”
Section: Principles Of Electrolytic Seawatermentioning
confidence: 99%
“…Liu et al have demonstrated that higher concentrations of transition metal doping can prompt AEM to switch to LOM by controlling the distribution of Ru 4d and O 2p orbitals, as well as the adsorption energy of intermediates. [54] Overall, the focus of these studies is based on activity regulation, that is, the transition from AEM to LOM. However, more research is needed to investigate the problem of stability degradation caused by a bias towards the LOM mechanism.…”
Section: Coordinated Relations Of Catalytic Mechanismsmentioning
confidence: 99%